Sensor node clutter distribution in LoRa LPWAN - Zainal, Nur Aishah; Habaebi, Mohamed Hadi; Chowdhury, Israth Jahan; Islam, Md. Rafiqul (2017)
Low Power WAN (LPWAN) is a wireless broad area network technology. It is interconnects using only low bandwidth, less power consumption but at a long range. This new technology is operate in unauthorized spectrum [1] which designed for wireless data communication. In order to have an insight of such long range technology, this paper evaluates the performance of LoRa radio links under shadowing effect and realistic smart city utilities clutter grid distribution. Such environment is synonymous to residential, industrial and modern urban centers. The focus is to include the effect of shadowing on the radio links while attempting to study the optimum sink node numbers and their locations for maximum sensor node connectivity. Results indicate that the usual unrealistic random node distribution does not reflect actual real-life scenario where many of these sensing nodes follow the built infrastructure around the city of smart buildings. The system is evaluated in terms of connectivity and packet loss ratio.